1983
DOI: 10.1016/s0022-5347(17)51746-2
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Adenoma of the Bladder After Kidney Transplantation: Spontaneous Improvement with Azathioprine Removal; Surgical Trauma and Cytomegalovirus Infection as Possible Etiologic Factors

Abstract: We report 2 cases of nephrogenic adenoma several years after successful cadaver kidney transplantation. In 1 case the lesion had cytomegalovirus inclusions, and we observed a marked and sustained reduction in the extension of the lesion with cessation of azathioprine. Surgical trauma and cytomegalovirus infections are discussed as etiologic factors. Conservative treatment seemed appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6] They occur in patients with chronic bladder inflammation or previous genitourinary surgery, and they are particularly frequent in renal-transplant recipients. [7][8][9][10][11][12][13][14][15][16] The pathogenesis of these lesions is enigmatic. The favored hypothesis is that nephrogenic adenomas are metaplastic alterations of resident urothelial tissue, and therefore N the term "nephrogenic metaplasia" is used synonymously.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] They occur in patients with chronic bladder inflammation or previous genitourinary surgery, and they are particularly frequent in renal-transplant recipients. [7][8][9][10][11][12][13][14][15][16] The pathogenesis of these lesions is enigmatic. The favored hypothesis is that nephrogenic adenomas are metaplastic alterations of resident urothelial tissue, and therefore N the term "nephrogenic metaplasia" is used synonymously.…”
mentioning
confidence: 99%
“…The documentation of chronic inflammation, cal culi, rupture, trauma, catheterization and different sur gical interventions in the history of patients with this lesion indicate that it is the response of urothelium to tissue injury [2][3][4][5][6][7]. Nephrogenic adenoma have also been described in bladders with malakoplakia and car cinoma, after immunosuppression for renal transplanta tion, and following intravesical chemotherapy [1,7,8,13], Only Billis [14] and de Jong and Scholtmeijer [10] considered it a congenital anomaly. In our case, the tumor arised 4 years after surgical correction of preex isting urogenital abnormalities and recurrent urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the surgical procedure of ureter implantation cannot solely explain the high incidence of NA in renal transplantation patients. Beaudry et al [2] reported a case with partial regression of NA after the discontinuation of azathioprine and in which immunosuppression was considered to be the cause of NA. However, other studies reported conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…However, no evidence of NA was noted in these two cases. CMV infection has been referred to as an etiological factor in two previously reported cases of bladder NA [2,3], based on the demonstration of CMV inclusions within the tubular epithelial cells of NA. But the recent studies of Fournier et al [4] and Banyai-Falger et al [l] involving nine and seven cases of NA, respectively in the bladder of renal transplantation recipients suggested that NA is not related to CMV disease.…”
Section: Discussionmentioning
confidence: 99%